“It’s just Arabic!”: Linguistic Anxiety and Identity Negotiations in Egypt’s International Schools - Noha Roushdy (Revue des Mondes Musulmans et de la Méditerranée)
This paper examines the tensions around Arabic language education in Egypt’s expanding private international educational field. Drawing on interviews and participant-observation research inside an international school in Cairo between 2016-2017, I focus on the institutional, pedagogical, and sociocultural configuration of Arabic language education in international schools. I argue that students’ linguistic attitudes and practices echoed the sharp division between Standard and Egyptian Vernacular Arabic in the linguistic ideology of formal Arabic education. The research showed that lack of proficiency in Standard Arabic had no bearing on international school students’ academic achievement or social life. Conversely, students’ relationship to Egyptian Vernacular Arabic was central in everyday identity negotiations in the international school and provided a dynamic linguistic and cultural repertoire for the enactment of nationally inflected social and cultural values.